2021
DOI: 10.3390/su13084120
|View full text |Cite
|
Sign up to set email alerts
|

Application of Machine Learning Techniques in Injection Molding Quality Prediction: Implications on Sustainable Manufacturing Industry

Abstract: With sustainable growth highlighted as a key to success in Industry 4.0, manufacturing companies attempt to optimize production efficiency. In this study, we investigated whether machine learning has explanatory power for quality prediction problems in the injection molding industry. One concern in the injection molding industry is how to predict, and what affects, the quality of the molding products. While this is a large concern, prior studies have not yet examined such issues especially using machine learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 53 publications
0
24
0
1
Order By: Relevance
“…However, it is vital to understand that optimization methods that depend exclusively on CAE simulation data are not 100% accurate as they do not fully capture all the physics involved in polymer processing. For that reason, research has been conducted in predicting occurrences within injection molding by developing predictive frameworks [18,19] and including real experimental data as training data. For example, Saad Mukras' optimization framework, based on the Kriging Model, predicted cycle time, warpage, and volumetric shrinkage with an error of 6.7%, 3.2%, and 8%, respectively, by analyzing samples from real injection molding trials.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, it is vital to understand that optimization methods that depend exclusively on CAE simulation data are not 100% accurate as they do not fully capture all the physics involved in polymer processing. For that reason, research has been conducted in predicting occurrences within injection molding by developing predictive frameworks [18,19] and including real experimental data as training data. For example, Saad Mukras' optimization framework, based on the Kriging Model, predicted cycle time, warpage, and volumetric shrinkage with an error of 6.7%, 3.2%, and 8%, respectively, by analyzing samples from real injection molding trials.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Saleh et al [12] identify that the variables that have the most impact on the injection process are melt temperature, plastification time, maximum pressure, mold wall temperature, and injection time. Jung [9] concluded that temperature, injection time, and cycle time are important variables commonly selected by machine learning techniques. As we can see in these and other research works, there are variables that are transversal in the researcher's opinion to be monitored.…”
Section: Related Workmentioning
confidence: 99%
“…This means that other types of approaches may have been considered to complement the analysis. Lately, studies are not restricted only to the use of separate machine learning methods but have started to integrate the use of combinations of methods (ensemble methods [15]) and also the use of deep learning techniques such as, for example, autoencoders, to improve the efficiency of classification/regression [9], [16]. Thus, in this work, we compare different classifiers, the use of ensemble methods, and a first approach to the use of a deep learning technique to solve classification problems directly related to the injection process.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…To execute a given task, machine learning employs several algorithms or models. These algorithms are mostly used in several elds, including medical prediction (1)(2)(3), psychology (4,5), object recognition (6-8), quality monitoring (9) industry (10)(11)(12), and many other domains. However, our technical work focus is on the application of several algorithms to anticipate and classify diverse sorts of industrial process failures utilizing machine learning approaches.…”
Section: Introductionmentioning
confidence: 99%